(untitled) (European journal of volunteering and community-based projects, 2022)
Citizen participation is one of the approaches on which New Public Management and New Public Governance are based and can be qualified as a community-based tool in the management of public administration or common goods (Strokosch & Osborne, 2020; Brescia, 2020; Secinaro et al., 2022). As a result of COVID-19, Europe may have changed and has identified new strands, approaches, and concepts that require the attention of scholars. Therefore, the analysis of reality can provide a greater vision in a stormy period than the analysis of academic literature alone could give. If in the business, management, and economics sector, we have a restructuring of approaches, systems, and contexts (Campra, Esposito & Brescia, 2020). The expectation is that there will be changes and priorities also in public participation that are different from those identified in the literature (Massaro et al., 2021). Therefore, from the results of NEXIS UNI, news, law, and business database (Knap, 2018), all the results have been identified in the magazines from 2021 to 2022 in which we talk about citizen participation, public participation, and citizen involvement. The identification of the times focused on the context of European sources and news only. The analysis identified and eliminated the duplicates, with 2529 results in English and Italian. The content analysis conducted allows, with an objective method, to identify the primary key concepts (Secinaro et al., 2021). The software adopted for the analysis of the results is LEXIMANCER, which allowed the grouping based on the frequency with which the concepts appear in the text and the significance of the relationship of the elements expressed. Significance in the relationship between concepts also defines relationships and representation (Smith & Humphreys, 2006; Dal Mas, 2019; Secinaro et al., 2021a).